Zircon Dates Long‐Lived Plume Dynamics in Oceanic Islands. (28th October 2022) - Rojas‐Agramonte, Yamirka; Kaus, Boris J. P.; Piccolo, Andrea; Williams, Ian S.; Gerdes, Axel; Wong, Jean; Xie, HangXian; Buhre, Stephan; Toulkeridis, Theofilos; Montero, Pilar; Garcia‐Casco, Antonio
Abstract: In this contribution we report the first systematic study of zircon U‐Pb geochronology and δ 18 O‐ ε Hf( t ) isotope geochemistry from 10 islands of the hot‐spot related Galapagos Archipelago. The data extracted from the zircons allow them to be grouped into three types: (a) young zircons (0–∼4 Ma) with ε Hf( t ) (∼5–13) and δ 18 O (∼4–7) isotopic mantle signature with crystallization ages dating the islands, (b) zircons with ε Hf( t ) (∼5–13) and δ 18 O (∼5–7) isotopic mantle signature (∼4–164 Ma) which are interpreted to date the time of plume activity below the islands (∼164 Ma is the minimum time of impingement of the plume below the lithosphere), and (c) very old zircons (∼213–3, 000 Ma) with mostly continental (but also juvenile) ε Hf( t ) (∼−28–8) and δ 18 O (∼5–11) isotopic values documenting potential contamination from a number of sources. The first two types with similar isotopic mantle signature define what we call the Galápagos Plume Array (GPA). Given lithospheric plate motion, this result implies that GPA zircon predating the Galápagos lithosphere (i.e., >14–164 Ma) formed and were stored at sublithospheric depths for extended periods of time. In order to explain these observations, we performed 2D and 3D thermo‐mechanical numerical experiments of plume‐lithosphere interaction which show that dynamic plume activity gives rise to complex asthenospheric flow patterns and results in distinct long‐lasting mantle domains beneath a moving lithosphere. This demonstrates that it is physically plausible that old plume‐derived zircons survive at asthenospheric depths below ocean islands. Key Points: Our data define the Galápagos Plume Array defined by mantle ε Hf( t ) and δ18O values in the range ∼0–164 Ma This finding allows dating back plume activity to, at least, early Middle Jurassic (∼164 Ma) Numerical experiments confirm it is plausible that old Plume‐derived zircons survive in the asthenosphere for extended periods of time